Enhanced Solubility and Biological Activity of Dexibuprofen-Loaded Silica-Based Ternary Solid Dispersions - Muhammad Asim; Marriam Nazir; Zunera Chauhdary; Muhammad Irfan; Syed Haroon Khalid; Sajid Asghar; Usra; Raed I. Felimban; Mohammed A Majrashi; Mohannad S. Hazzazi; Mohammed Alissa; Safa H Qahl; et al. (Pharmaceutics, 2023)
The current study was designed to formulate ternary solid dispersions (TSDs) of dexibuprofen (Dex) by solvent evaporation to augment the solubility and dissolution profile, in turn providing gastric protection and effective anti-inflammatory activity. Initially, nine formulations (S1 to S9) of binary solid dispersions (BSDs) were developed. Formulation S1 comprising a 1:1 weight ratio of Dex and Syloid 244FP® was chosen as the optimum BSD formulation due to its better solubility profile. Afterward, 20 TSD formulations were developed using the optimum BSD. The formulation containing Syloid 244FP® with 40% Gelucire 48/16® (S18) and Poloxamer 188® (S23) successfully enhanced the solubility by 28.23 and 38.02 times, respectively, in pH 6.8, while dissolution was increased by 1.99- and 2.01-fold during the first 5 min as compared to pure drug. The in vivo gastroprotective study in rats suggested that the average gastric lesion index was in the order of pure Dex (8.33 ± 2.02) > S1 (7 ± 1.32) > S18 (2.17 ± 1.61) > S23 (1.83 ± 1.04) > control (0). The in vivo anti-inflammatory study in rats revealed that the percentage inhibition of swelling was in the order of S23 (71.47 ± 2.16) > S18 (64.8 ± 3.79) > S1 (54.14 ± 6.78) > pure drug (18.43 ± 2.21) > control (1.18 ± 0.64) after 6 h. ELISA results further confirmed the anti-inflammatory potential of the developed formulation, where low levels of IL-6 and TNF alpha were reported for animals treated with S23. Therefore, S23 could be considered an effective formulation that not only enhanced the solubility and bioavailability but also reduced the gastric irritation of Dex.